Metaheuristics for household refuse collection - Nunes, Ana Catarina; Cortinhal, M.J.; Mourão, Maria Cândida (Euro XXV - 25th European Conference on Operational Research, 2012)
The household refuse collection in large urban areas may be modeled by the sectoring-arc routing problem (SARP). The SARP groups two families of problems: sectoring (or districting) problems and capacitated arc routing problems (CARP). The SARP is defined over a mixed graph. Its aim is to identify a given number of similar sectors (sub-graphs) and to build a set of collecting trips in each sector, such that the total duration of the trips is minimized. Metaheuristics are presented, and computational results over a set of benchmark instances are reported.